Plasma Deposited Polyoxazoline Films Integration Into Spiral Microfluidics for the Targeted Capture of Size Selected Cells - Gheorghiu, Alexandru A.; Muguet, Ines; Chakiris, James; Chan, Kit Man; Priest, Craig; Macgregor, Melanie (Frontiers in Chemistry, 2021)
Biomolecules readily and irreversibly bind to plasma deposited Polyoxazoline thin films in physiological conditions. The unique reactivity of these thin films towards antibodies is driving the development of immunosensing platforms for applications in cancer diagnostics. However, in order for these coatings to be used as advanced immunosensors, they need to be incorporated into microfluidic devices that are sealed via plasma bonding. In this work, the thickness, chemistry and reactivity of the polyoxazoline films were assessed following plasma activation. Films deposited from methyl and isopropenyl oxazoline precursors were integrated into spiral microfluidic devices and biofunctionalized with prostate cancer specific antibodies. Using microbeads as model particles, the design of the spiral microfluidic was optimised to enable the size-based isolation of cancer cells. The device was tested with a mixed cell suspension of healthy and malignant prostate cells. The results showed that, following size-specific separation in the spiral, selective capture was achieved on the immunofunctionalised PPOx surface. This proof of concept study demonstrates that plasma deposited polyoxazoline can be used for immunosensing in plasma bonded microfluidic devices.